Perbaikan Usability pada Aplikasi Goopo dengan Menggunakan Metode System Usability Scale (SUS) - Habib Reza Pahlawan; Amaranti, Reni; Nurrahman, Ahmad Arif (UNISBA Press, 2024)
Abstract. Over time, technology has become crucial for obtaining information. Consumer behavior is rapidly changing, necessitating that everything be done quickly and easily. This makes mobile applications for customer services essential for business sustainability. Therefore, the Goopo app was developed to meet customer needs. PT. Inovasi Digital Indonesia (Goopo) recognized this opportunity and created an application that allows consumers to easily transact and monitor products in real time. Goopo is a company engaged in cattle and sheep farming, offering services such as the Cattle Farming Business Program (PUTS), Sheep Farming Business Program (PUTD), as well as Aqiqah and Qurban services. This study aims to evaluate and improve the usability of the Goopo mobile application using the System Usability Scale (SUS) method. The study involved 30 respondents who are active users of the Goopo application and collected suggestions for improvements through direct interviews. The research seeks to enhance usability by improving the user interface (UI) and system features. Specific recommendations for improvement include adjustments to the homepage layout, the addition of navigation buttons, notification features, and more detailed information about the programs offered. The development of the Goopo application is aimed at increasing usability so that it can be enjoyed by users of all ages. Test results show that the Goopo application has an average SUS score of 70, which falls into the